Whither international trade policies? Worries about continuing protectionism - Juergen B. Donges (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1986)
The eighties should have seen further progress in the liberalization of international trade. During the Tokyo Round of trade policy negotiations (completed in 1979) an agreement on tariff reductions was reached and several "Codes of Conduct" were set up with the aim of stopping the proliferation of non-tariff restrictions and thereby providing for stability and predictability of trade rules. But by now it has become evident that the Tokyo Round marked a turning point in the post-war development towards liberalization. The failure of the GATT Ministerial Meeting in November 1982, mainly due to the clash between the United States and the European Community (and France) over a credible commitment to roll back import restrictions and to curb export subsidies, was a clear indication that the spirit of free trade was fading away. Subsequently, we have witnessed a strong revival of protectionism in the United States - the country which had led the trade liberalization process in the post-war period. Whether the recent meeting of trade ministers in Punta del Este (Uruguay) has laid the foundations of a new liberalization era remains to be seen. The next section highlights recent developments in trade policies, in particular the continued drift into protectionism. It should become clear where countervailing efforts, through a new round of multilateral trade negotiations within GATT (to begin in 1987), are of greatest need. Subsequently, the consequences of current protectionism are recalled, both for the protecting countries themselves and for the world economy as a whole. This is followed by a brief discussion of the causes of observable clashes between international economists' prescriptions and the conduct of trade policies in practice. The last section addresses the prospects for restoring a functioning world trading order.
Keywords: 330; Außenwirtschaftspolitik; Protektionismus